2019
DOI: 10.1108/cg-07-2018-0250
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Anglo-American corporate governance and its impact on financial market growth: a comparative analysis of nineteen developing countries 1995-2014

Abstract: Purpose Since the late 1990s, developing countries have been encouraged by international financial organisations to adopt a shareholder primacy corporate governance model. It was anticipated that in an increasingly globalised financial market, countries which introduced corporate governance practices that favour investors would gain a comparative advantage and attract more capital leading to financial market growth. This paper aims to empirically test this hypothesis. Design/methodology/approach The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 181 publications
(137 reference statements)
1
9
0
1
Order By: Relevance
“…Similarly, the association between corporate governance attributes and financial distress varies from country to country. As an Asian emerging market, corporate governance mechanism in Pakistan has featured with unique institutional background, concentrated ownership, family controlled firms and Anglo-governance model create a different environment business than the business environment of development countries (Samanta, 2019). Conversely, limited studies are available on the association between corporate governance and firm financial distress in the context of Asian markets, specifically in Pakistani context.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the association between corporate governance attributes and financial distress varies from country to country. As an Asian emerging market, corporate governance mechanism in Pakistan has featured with unique institutional background, concentrated ownership, family controlled firms and Anglo-governance model create a different environment business than the business environment of development countries (Samanta, 2019). Conversely, limited studies are available on the association between corporate governance and firm financial distress in the context of Asian markets, specifically in Pakistani context.…”
Section: Introductionmentioning
confidence: 99%
“…They found that changes in crude oil price had negative impacts on the stock markets of petroleum-importer countries but had positive impacts on petroleum-export countries [17]. By using the generalized autoregressive conditional heteroscedasticity (GARCH) model, the Granger causality test, and a vector autoregression model, follow-up studies confirmed that oil price fluctuation had an evident spillover effect on the stock markets in developed countries and emerging economic entities [11,[18][19][20].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Selain itu, mekanisme tata kelola perusahaan, sistem hukum dan persyaratan pengungkapan keuangan berbeda dan bervariasi di pasar negara berkembang jika dibandingkan dengan Negara maju. Demikian pula dengan keterkaitan antara atribut tata kelola perusahaan dan kesulitan keuangan bervariasi dari satu negara ke negara lain (Samanta, 2019;Younas et al, 2021). Oleh karena itu, paper ini akan mengungkapkan bukti empiris mengenai pengaruh corporate governance atau tata kelola perusahaan terhadap kesulitan keuangan.…”
Section: Pendahuluanunclassified